EVALUATION OF MODIFIED MILLARD'S TECHNIQUE WITH PREMAXILLA SHORTENING IN BILATERAL LABIOPLASTY AT MALAHAYATI HOSPITAL BANDA ACEH 2016- 2019 - Taufik, Muhammad; Jailani, Muhammad (Jurnal Rekonstruksi dan Estetik, 2019)
Highlights: The use of a modified Millard technique with premaxillary shortening in cleft lip and palate (CLP) reconstructive surgery. A majority of patients achieved positive results in bilateral labioplasty when the modified Millard technique with premaxillary shortening was employed. Abstract:  Introduction: Cleft Lip and Palate (CLP) is a congenital abnormality in the form of gaps in the lips, gums and palate. Surgical techniques for reconstructive surgery vary greatly, but labioplasty using a modified millard technique with premaxillary shortening is a technique that we used in this study with the aim of premaxilla shortening to reduce the tension of the suture wound and will reduce the scar formed in Bilateral labioplasty after surgery. Methods: This research is a cohort  with  a  retrospective  approach conducted on labioplasty patients at Malahayati Hospital in Banda Aceh, which was handled in the period of 2016 - 2019. The sample amounted to 23 respondents who will be analyzed  using  the  frequency distribution table. Results: The study found male sex as much as 60.9%, the age of patients in the age group 2 years and over as much as 69.6%, 6-9 months evaluation time as much as 87.0%, the diagnosis of complete bilateral labioplasty as much as 65.2% and good outcome in bil ateral labioplasty using modified Millard technique with premaxilla shortening as much as 73.9%. Conclusion: The majority of male sex is the most, the highest in the age group 2 years and above, the most evaluation time is 6-9 months, the most common diagnosis is complete bilateral labiolasty and the most results on bilateral labioplasty using modified millard techniques with premaxillary shortening is good outcome.